The Chameleon public seating / Lu’lu Ilma Nafia, Halisa Legowo and Pandu Purwandaru - Nafia, Lu’lu Ilma; Legowo, Halisa; Hassin, Pandu Purwandaru (2024)
This project aims to create a public seating design that harmonizes with nature by collaborating Malay vernacular technology with contemporary advancements. The methodology involves an in-depth investigation of Malay vernacular culture and the integration of modern wind turbine technology. The research seeks to identify how traditional elements can be effectively combined with cutting-edge innovations to produce functional and aesthetically pleasing public furniture. The outcome of this project is a piece of furniture that exemplifies a successful collaboration between traditional Malay techniques and contemporary technology. This hybrid design not only respects cultural heritage but also embraces sustainable practices through the use of renewable energy sources. The findings highlight the potential of incorporating vernacular wisdom into modern design, demonstrating that such an approach can result in sustainable and visually appealing solutions. This project underscores the importance of interdisciplinary collaboration in design, showcasing how traditional knowledge and modern technology can coexist and enhance each other, ultimately contributing to environmentally friendly and culturally sensitive public spaces.